Development of an Acute Biotic Ligand Model for Ni Toxicity to Daphnia pulex in Soft Water: Effects of Ca, Mg, Na, K, Cl, pH and Dissolved Organic Matter - Kozlova, Tatiana A. (My University, 2007)
In this study the influence of several water chemistry parameters on the toxicity of Ni to Daphnia pulex in soft water were tested. A reconstituted soft water (pH 7.8, hardness 31.5 mg/L CaCO3) was used as the basis for culture and testing. Daphnia pulex was chosen as a typical cladoceran, one which can be acclimated to very soft water. An understanding of the influence of water chemistry on Ni toxicity in soft water is relevant because metals have higher bioavailability in soft water. The 48h EC50 in the reconstituted soft water (RSW) was 974 μg/L (16 μM) dissolved Ni (95%CI 830- 1081 μg/L). The following factors were examined for their potential for modifying Ni toxicity: Ca, Mg, Na, K, Cl, pH (3 different approaches used) and natural organic matter (NOM, 2 sources tested). Both Ca and Mg protected against Ni toxicity and the relative effect was greater for Ca. Varying the concentrations of Na, Cl or K did not alter the toxicity of Ni. Tests at different pH showed that as pH increased, Ni toxicity decreased. When the test solution pH was adjusted with the organic buffer 3-morpholinepropanesulfonic acid, there was a clear correlation between increasing pH and increasing EC50. The pH tests using bicarbonate to adjust pH did not show this relationship as clearly. Both types of NOM showed a protective effect on Ni toxicity with Nordic Reservoir NOM having a 4 fold greater effect than that of Suwannee River NOM. This research illustrated that the effect of alterations in water chemistry were generally as predicted within the context of the biotic ligand model (BLM) approach. The data provide the information required to develop a BLM for the acute effects of Ni in soft water.
Keywords: acute biotic ligand model, Ni toxicity, Daphnia pulex, soft water, alkalinity, dissolved organic matter, NOM